The Role of Social Media in Activating the Extracurricular Activities of the Ninth Grade English language from the Teachers’ Point of View in Jordan - Attoun, Nour Ali Mousa; Al-Jadiri, Adnan (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to identify the role of social media in activating the extra- curricular activities of ninth grade students in English language from the teacher's point of view in Jordan. The descriptive analytical approach was adopted through a sample of (45) male and (83) female teachers.The study tool consisted of (40) items, and the validity was verified by presenting it to a panel of arbitrators. The reliability coefficient was extracted and it reached (0.75) for each Test – Re test internal consistency reliability.The statistical analysis process reached the following results:There is a role for social media in activating extracurricular activities in the English language for the ninth grade from the point of view of teachers in Jordan.It was also found that the items that received a high level amounted to (33) items, as for the items that received medium level, there were (7) items.The study recommended the necessity for activating the extracurricular activities so that it is invested within the time of classes of all kinds and goes outside the time allocated for the class to achieve integration in education.
Keywords: Social Media; Activating Extracurricular Activities; English Language